VD_FINDINFO Décision / 2013 / 706 vom 5. August 2013 - VD Tribunal cantonal (2013)
ASSISTANCE JUDICIAIRE, PLAIGNANT, INTÉRÊT JURIDIQUEMENT PROTÉGÉ, DÉCISION SUR FRAIS | 180 al. 1 CP, 181 CP, 217 al. 1 CP, 22 al. 1 CP, 136 CPP (CH), 137 CPP (CH), 382 al. 1 CPP (CH), 393 CPP (CH)